Ozone generation by pulsed streamer discharge in air - Buntat, Zolkafle (Canadian Center of Science and Education, 2009)

(untitled)
Ozone is well established as an important oxidising agent in many industrial applications and the high-voltage pulsed streamer discharge technique has emerged as an efficient method for its production. The paper investigates the parameters that are important in this process, including the magnitude of the applied pulse voltage, the air flow rate and the electrode dimensions and spacing, when used in a plate-to-plate reactor configuration in which sheets of perforated aluminium are employed to enhance the degree of ionisation and soda lime glass dielectric barriers both to inhibit singular discharges and to promote the development of the streamer discharge. The highest ozone concentration achieved was 5995 ppmv and the greatest yield was 144 g/kWh.